Расчет показателей разработки месторождения на завершающей стадии эксплуатации - Шеина, З. В.; Голубенко, В. П.; Мусиенко, О. В. (НТУ "ХПИ", 2015)
Представлений алгоритм розрахунку показників розробки родовища на завершальній стадії експлуатації в умовах впровадження заходів, пов'язаних із оптимізацією роботи газозбірної та газотранспортної системи.

The method of estimation is presented based on the formula Adamova and taking into the account the effluence of gathering and processing systems parameters. The article also shows the results of calculations for the one of the oldest field in Western Ukraine region.
Method of production parameters estimation for the gas field at the final stage of development
Keywords: скважины; бурение; пробковые горизонты; эксплуатационные горизонты; очистка газопроводов; рабочее давление